Causal selection and counterfactual reasoning/ selección causal y razonamiento contrafactual/ seleção causal e raciocínio contrafactual (2013)
In this paper I defend the view that counterfactual thinking depends on our causal representation of the world, and in this sense, I argue that causal and counterfactual reasoning are tightly linked. I offer some criticisms and experimental evidence against Mandel's judgement dissociation theory (Mandel, 2003b), which claims functional independence between the process of causal selection and counterfactual reasoning in the context of causal selection. In the experiments described, I manipulated some elements of the semantics of the task to show the cases in which dissociation between causal and counterfactual reasoning does not occur. In Experiment 1, the level of description of the target event is manipulated in a list generation and rating task. Experiment 2 replicates Experiment 1 findings using an alternative coding system, whereas Experiment 3 does the same using an alternative answer format. The results of the experiments support the picture of causal understanding proposed by the causal mental models.